2007
DOI: 10.1590/s0074-02762007005000073
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of bovine tuberculosis in a Brazilian herd (São Paulo)

Abstract: Mycobacterium was verified in animals from a Brazilian dairy herd, a total of 42 samples from 30 cows were submitted to culture and the isolated strains were analyzed by two polymerase chain reaction (PCR), the first specific for species belonging to the Mycobacterium complex (MTBC) (Bouvet et al. 1993). From a clinical and epidemiological perspective, a rapid method to differentiate both species is important for timely diagnosis, effective treatment (due to the intrinsic resistance of M. bovis to pirazynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The culture used in these studies was the most sensitive test. However, the results obtained in this study were similar to those observed in the study in a dairy herd of Tatuí, Brazil, which showed 60% (18/30) of the positive samples in the culture (NASSAR et al, 2007). Two samples were negative by PCR analysis even with suggestive colonies in the culture were identified.…”
Section: Discussionsupporting
confidence: 89%
“…The culture used in these studies was the most sensitive test. However, the results obtained in this study were similar to those observed in the study in a dairy herd of Tatuí, Brazil, which showed 60% (18/30) of the positive samples in the culture (NASSAR et al, 2007). Two samples were negative by PCR analysis even with suggestive colonies in the culture were identified.…”
Section: Discussionsupporting
confidence: 89%
“…In one study using infected human blood samples, the sensitivity of the IS1081 PCR assay was only 43.75% [9]. However, when the latter assay was applied in the identification of M. bovis culture isolates, it identified 27 out of 27 (100%) of the isolates [17]. This indicates that although the assay was not very sensitive in the present study, it could nonetheless be a sensitive assay in the detection of M. bovis.…”
Section: Discussionmentioning
confidence: 61%
“…In Ecuador's dairy areas, 90% of the cattle in the highlands are Holstein Friesian, whereas in the tropical areas, the main breeds used for milk production are Jersey, Brown Swiss, and crossbreeds. The differences in BTB prevalence among cattle breeds and geographic areas present in Ecuador, were also found in the slaughterhouses of Argentina (9), Brazil (53,54), and Mexico (55,56).…”
Section: Veterinary Inspectionmentioning
confidence: 72%